EFFECT OF DIMETHOATE ON THE LEVEL OF GLYCOGEN IN TISSUES OF FRESHWATER FISH PUNTIUS TICTO (HAM) - R. M. GANESHWADE; S. M. PAWAR; S. R. SONAWANE; K. D. DEVARAROO; V. B. SUTAR (The Bioscan, 2011)
Freshwater fish Puntius ticto, exposed to lethal and two sublethal concentrations (5.012ppm; 2.506 ppm and 1.253ppm) of dimethoate for 96hr and 60 days respectively. Glycogen content was analyzed from different tissues after exposure period. The significant decrease in the glycogen content was observed in gills, kidney and brain; moderate decline in gonads, muscles and slight changes takes place in liver and intestine.